1999
DOI: 10.1161/01.str.30.11.2366
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Air Medical Transportation After Tissue Plasminogen Activator Administration in Acute Ischemic Stroke

Abstract: Background and Purpose-We sought to determine the safety of air medical transport (AMT) of patients with acute ischemic stroke (AIS) immediately after or during administration of tissue plasminogen activator (tPA). Patients with AIS treated with tPA in nonuniversity hospitals frequently need transfer to tertiary care centers that can provide specialized care. AMT is a widely available mode of transport that is crucial in providing expedient and quality health care to critically ill patients while assuring high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…18 A comparison of ground vs air transport showed that 22.3%, 43.2%, and 55.4% of Americans have access to a stroke center within 30, 45, and 60 minutes, respectively. 19 The use of air ambulances would increase access to 26.0%, 65.5%, and 79.3% within 30, 45, and 60 minutes, respectively. 19 This was confirmed by another study comparing helicopter transport of 94 patients with AIS treated with IV-rtPA to 28 patients transferred by ground.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 A comparison of ground vs air transport showed that 22.3%, 43.2%, and 55.4% of Americans have access to a stroke center within 30, 45, and 60 minutes, respectively. 19 The use of air ambulances would increase access to 26.0%, 65.5%, and 79.3% within 30, 45, and 60 minutes, respectively. 19 This was confirmed by another study comparing helicopter transport of 94 patients with AIS treated with IV-rtPA to 28 patients transferred by ground.…”
mentioning
confidence: 99%
“…19 The use of air ambulances would increase access to 26.0%, 65.5%, and 79.3% within 30, 45, and 60 minutes, respectively. 19 This was confirmed by another study comparing helicopter transport of 94 patients with AIS treated with IV-rtPA to 28 patients transferred by ground. Total air transport time was significantly less than ground transport time (54 vs 69 minutes; p ϭ 0.04).…”
mentioning
confidence: 99%
“…The transportation cost varied from $2214 to $4500. Chalela et al 8 showed the safety of air medical transport of these patients. A similar benefit was seen in acute trauma patients.…”
Section: Outcomementioning
confidence: 99%
“…21 The overall cost-effectiveness of helicopter emergency medical services in improving outcomes has been shown in other countries. 8,9,21 A future strategy would be to improve air transport of acute stroke patients to stroke centers. Our study has shown that hospitals spend more on patients who are referred from other centers for intervention, and the outcome of patients directly admitted is better than that of patients transferred in from another facility.…”
Section: Outcomementioning
confidence: 99%
“…57 Air medical transport may reduce transit times, may increase the availability of thrombolytic therapy to residents of rural communities, 58 and may be cost-effective. 59,60 The air medical evacuation of a stroke patient in the prehospital setting could be considered if both of the following conditions are present: 51 1. The closest facility capable of providing treatment to the patient with an acute stroke is more than an hour away by ground ambulance.…”
Section: Emerging Alternative: Air Medical Transportmentioning
confidence: 99%